Ranking political science programs: a view from the lower half. - Katz, Richard S.; Eagles, Munroe (PS: Political Science & Politics, 1996)
Part of a special section on the National Research Council's relative rankings of political science departments within U.S. colleges and universities. The writers contend that rating academic departments, as the National Research Council has done, can be modeled successfully and parsimoniously with a six-variable model of the “determinants of ratings success.” They estimate the parameters of this six-variable model and demonstrate that the most statistically robust and important predictor of ratings success—department size—mirrors a characteristic of departments that is beyond departmental control and that has no direct bearing on the quality of the departments concerned. They conclude that it may be wiser to evaluate departments within the constraints imposed by their size.